MYCOTOXINS IN POULTRY FEED AND FEED INGREDIENTS IN SULAYMANIYAH, KURDISTAN REGION OF IRAQ - H. M. Rahim; D.H. Othman; R. K. Majeed; N.M. Saeed; D. O. Ismaeel (Basrah Journal of Veterinary Research)
Mycotoxins are fungal metabolic byproducts that can contaminate animal feedand human food. To investigate the incidence of mycotoxins in poultry feed inSulaymaniyah Governorate, Iraq, 173 samples of feed (n =150) and feed ingredients(n = 23) were collected from 49 poultry farms and feed mills. The samples wereanalyzed to quantitatively determine the existence of five mycotoxins, namelyaflatoxin, fumonisin, ochratoxin, T-2, and zearalenone, using specific kits. All thetested samples contained ochratoxin at concentrations ranging between 1.0 and 6.0μg/kg and averaging 3.4 ± 0.1 μg/kg. About 94.8% of the feed and feed ingredientsamples contained a minimum of four mycotoxins in different concentrations. Thereis a need to understand the cumulative toxic effects better when several mycotoxinsoccur in animal feed, which may result in issuing new regulations about the maximumallowed concentrations of mycotoxins in feedstuff.